2007
DOI: 10.1128/mcb.00227-07
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin and TRAF Family Proteins Regulate Reactive Oxygen Species-Dependent Activation of ASK1 through Reciprocal Modulation of the N-Terminal Homophilic Interaction of ASK1

Abstract: Apoptosis signal-regulating kinase 1 (ASK1), a member of the mitogen-activated protein kinase kinase kinase family, plays pivotal roles in reactive oxygen species (ROS)-induced cellular responses. In resting cells, endogenous ASK1 constitutively forms a homo-oligomerized but still inactive high-molecular-mass complex including thioredoxin (Trx), which we designated the ASK1 signalosome. Upon ROS stimulation, the ASK1 signalosome unbinds from Trx and forms a fully activated higher-molecular-mass complex, in par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
237
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(268 citation statements)
references
References 23 publications
16
237
0
4
Order By: Relevance
“…Activation of ASK1 in cellular response to various stimuli including ROS requires ASK1 homo-oligomerization, recruitment of TRAF2 or TRAF6 to ASK1, and the autophosphorylation of a threonine residue in ASK1 (Thr 838 or Thr 845 of human or mouse ASK1, respectively) (19)(20)(21)(22)(23). These events may be potentially susceptible to modulation by ASK1-interacting proteins, among which thioredoxin was the first identified ASK1-inhibitory protein (4,7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of ASK1 in cellular response to various stimuli including ROS requires ASK1 homo-oligomerization, recruitment of TRAF2 or TRAF6 to ASK1, and the autophosphorylation of a threonine residue in ASK1 (Thr 838 or Thr 845 of human or mouse ASK1, respectively) (19)(20)(21)(22)(23). These events may be potentially susceptible to modulation by ASK1-interacting proteins, among which thioredoxin was the first identified ASK1-inhibitory protein (4,7).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of ASK1 requires ASK1 homo-oligomerization, recruitment of TRAF family proteins to ASK1, and the subsequent autophosphorylation of a threonine residue in the kinase domain of ASK1 (Thr 838 in the human ASK1) (19)(20)(21)(22)(23). We therefore examined a possible effect of CIB1 on those processes required for ASK1 activation.…”
Section: Cib1 Inhibits Traf2-ask1 Interaction and Ask1 Phosphorylatiomentioning
confidence: 99%
See 1 more Smart Citation
“…of an inhibitory N-terminal domain, an internal kinase domain, and a C-terminal regulatory domain (5,21,22). To determine which domain within ASK1 is crucial for 26 S proteasome inhibition, we expressed Ub G76V GFP along with full-length ASK1 (amino acids 1-1375), ASK1…”
Section: Ask1 Regulates 26 S Proteasome Through Two Separate Regionsmentioning
confidence: 99%
“…Immunoblot analyses of the eluted fractions with anti-20 S core, anti-19 S Rpt2, and anti-HA antibodies revealed that the components of the 20 S and 19 S proteasome co-eluted over the same range of high molecular weight fractions (fraction numbers [13][14][15][16][17][18][19][20][21][22][23][24][25], whereas ASK1 was present in the lower molecular weight fraction (fraction number [43][44][45][46][47][48][49][50][51][52][53][54][55] (Fig. 5F).…”
Section: Ask1 Interacts With Atpases Of 19 S Regulatory Particles Andmentioning
confidence: 99%